2021
DOI: 10.3390/su13084508
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Heavy Metal Content in Soil and Plants in the Dumping Ground of Magnesite Mining Factory Jelšava-Lubeník (Slovakia)

Abstract: A high content of heavy metals in the soil and plants of a magnesite mining area might cause serious damage to the environment and can be a threat to the health of the surrounding population. This paper presents the results of research that focused on analyzing the heavy metal content in soil and plants in the dumping grounds of the magnesite mining factory Jelšava-Lubeník (Slovakia). The analysis focused on the content of heavy metals in soil (X-ray fluorescence spectrometry, atomic absorption spectrometry), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 75 publications
5
9
1
Order By: Relevance
“…The measured values of Mg in the investigated areas exceeded the average values for the Slovak Republic by several times, while the maximum measured value in Jelšava-Lubeník exceeded the average value by 567 times, and in Košice by 451 times. These findings are consistent with previous studies by Fazekaš et al [67], Štofejova et al [66], and Štofejová et al [73], who found significant soil contamination with these potentially toxic elements in the studied areas, resulting in the formation of Mg(OH) 2 crusts and alkalization and salinization of the soil.…”
Section: Soil Reaction Soil Organic Matter and Total Content Of Poten...supporting
confidence: 93%
See 2 more Smart Citations
“…The measured values of Mg in the investigated areas exceeded the average values for the Slovak Republic by several times, while the maximum measured value in Jelšava-Lubeník exceeded the average value by 567 times, and in Košice by 451 times. These findings are consistent with previous studies by Fazekaš et al [67], Štofejova et al [66], and Štofejová et al [73], who found significant soil contamination with these potentially toxic elements in the studied areas, resulting in the formation of Mg(OH) 2 crusts and alkalization and salinization of the soil.…”
Section: Soil Reaction Soil Organic Matter and Total Content Of Poten...supporting
confidence: 93%
“…In Košice, the pH values ranged from 5.3 to 9.1, showing that the soils in this area are strongly acidic to strongly alkaline. Similar findings are reported in the studies of Yang et al [65], Štofejova et al [66], Fazekaš et al [67], and Hronec and Adamišin [68], who confirmed a strong alkalization of the soil in the areas of magnesite mining and processing. The current research clearly confirms the key role of organic carbon in the sorption of inorganic contaminants [69][70][71].…”
Section: Soil Reaction Soil Organic Matter and Total Content Of Poten...supporting
confidence: 90%
See 1 more Smart Citation
“…However, their chemical forms and bioavailability are changeable [2]. Therefore, they can accumulate in soil and remain persistent for long periods of time, posing serious environmental threats [2,3]. Rapid industrialization and urbanization have caused the discharge of wastewater containing high concentrations of HMs, which has contributed to the elevated levels of HMs in urban environments, especially in developing countries [4].…”
Section: Introductionmentioning
confidence: 99%
“…Residents in industrial areas are most vulnerable to exposure to HMs, since many of these elements are closely related to industry [5]. Growing evidence demonstrates that HM pollution in mining areas has caused serious health issues in local residents, as well as damage to soil health [3]. Therefore, the prevention of toxic effects from these contaminants has become an existential challenge [6].…”
Section: Introductionmentioning
confidence: 99%